Development of Learning Device based Ethnoscience for Heat Material in Kabupaten Tegal - Susilawati Susilawati; Nizar Setiawan; Nur Khoiri (Journal of Education and Learning (EduLearn), 2018)
The purpose of this research is produce learning set equipment on heat material of ethnoscience based in Tegal district, The results showed that the feasibility of syllabus-based ethnoscience include into the category is very good because it has a percentage of 96,43%. The feasibility learning device of an ethnoscience-based into a very good category because it has a percentage of 91,37%. Ethnoscience-based learning tool able to improve student learning outcomes from the average value of 42,82 to 80,06 and the gains value 0,65. While the questionnaire of student’s learning interest after the application of physics learning device on ethnoscience based heat material in Kabupaten tegal get the average value 3,01 with the high criteria.